Short message service (SMS) surveys assessing pre-exposure prophylaxis (PrEP) adherence and sexual behavior are highly acceptable among HIV-uninfected members of serodiscordant couples in East Africa: A mixed methods study - Muwonge, Timothy R.; Ngure, Kenneth; Katabira, Elly; Mugo, Nelly; Kimemia, Grace; O'Rourke Burns, Bridget Frances; Musinguzi, Nicholas; Bambia, Felix; Baeten, Jared M.; Heffron, Renee; Haberer, Jessica E. (AIDS and Behavior, 2019)
Short message service (SMS) surveys are a promising data collection method and were used to measure sexual behavior and adherence to HIV pre-exposure prophylaxis (PrEP) among HIV-uninfected partners of serodiscordant couples enrolled in a sub-study of the Partners Demonstration Project (an open-label study of integrated antiretroviral therapy and PrEP for HIV prevention in Kenya and Uganda). Questionnaires were completed by 142 participants after study exit. Median age was 29 years; 69% were male. Ninety-five percent (95%) felt SMS surveys were “easy” or “very easy”, 74% reported no challenges, and 72% preferred SMS surveys over in-person study visits. Qualitative interviews involving 32 participants confirmed the ease of responding to SMS surveys. Participants also indicated that surveys acted as reminders for adherence to PrEP and condom use and were experienced as support from the study. SMS surveys were generally found to be acceptable in this population and provided real-time context of PrEP use.
Keywords: Adherence; SMS; PrEP; Serodiscordant Couples